Boron‐Based Multi‐Resonance TADF Emitter with Suppressed Intermolecular Interaction and Isomer Formation for Efficient Pure Blue OLEDs. Issue 19 (10th March 2022) - Cheon, Hyung Jin; Shin, Youn‐Seob; Park, Noh‐Hwal; Lee, Jeong‐Hwan; Kim, Yun‐Hi
Abstract: Multi‐resonance (MR) thermally activated delayed fluorescent (TADF) emitters are highly attractive due to their superior color purity as well as efficient light‐harvesting ability from singlets and triplets. However, boron and nitrogen‐based MR‐TADF emitters suffer from their strong π–π interaction owing to their rigid flat cores. Herein, a boron‐based multi‐resonance blue TADF emitter with suppressed intermolecular interaction and isomer formation is developed through a simple synthetic process by introducing meta ‐xylene and meta ‐phenyphenyl groups to the core. The MR‐TADF emitter, mBP‐DABNA‐Me, shows a narrowband blue emission with a peak at 467 nm, along with full width at half maximum of 28 nm, and photoluminescence quantum yield of 97%. Notably, highly efficient pure blue organic light‐emitting diode (OLED) is realized using mBP‐DABNA‐Me, showing a maximum external quantum efficiency of 24.3% and a stable blue emission with a Commission Internationale de L'Eclairage coordinate of (0.124, 0.140). The color purity of the OLED is maintained at a high doping concentration of over 20%, attributed to the suppressed intermolecular interaction between the MR emitters. Abstract : A strategic substitution of the bulky groups effectively suppresses the intermolecular interaction and the formation of isomers in mBP‐DABNA‐Me. Therefore, the mBP‐DABNA‐Me based organic light‐emitting diode exhibits an efficiency of 24.3% with a pure blue emission, color‐coordinate of (0.124, 0.140). Notably, the substituents hinder the bathochromic shift, keeping the pure blue emission even at a high concentration of 25%.